Aspects of Fiscal Performance in Some Transition Economies Under Fund-Supported Programs - Buiter, Willem (Washington, D.C. : International Monetary Fund, 1997)
Key medium- and longer-term fiscal issues faced by transition economies are reviewed, including government solvency and the sustainability of the fiscal-financial-monetary program. The paper aims to assist the design and implementation of future Fund programs and to contribute to the debate about fiscal policy in transition economies. After presenting a framework for evaluating the sustainability of the fiscal-financial-monetary program of the state, some numerical material is presented on public debt, (quasi-) fiscal deficits and monetary financing. Eight budgetary issues of special relevance to transition economies are considered next. The lessons from this study are summarized in a number of propositions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet